Изучение истории Реформации и религиозных войн в трудах медиевистов Украины (1805 — первая половина 80-х гг. ХІХ в.) - Лиман, С.И. (My University, 2005)
S. Liman. History of Reformation and Religion Wars in the Studies of Medievists in Ukrainian Lands of Russian Empire, 1805–First Half of 1880s. Ukrainian medievists in 1805–first half of 1880s made a substantial contribution into the study of history of Reformation and Religion Wars. They studied the course of Reformation movement in several European countries: Germany, France, Switzerland, the Netherlands, Poland. The most outstanding results were attained by M. N. Petrov (history of the Great Farmers’ War in Germany), I. V. Luchitskiy (history of Reformation and Religion Wars in France), N. N. Lyubovich (history of Reformation in Poland). These studies met the level of their contemporary science, many of their findings preserving scientific value up to our days. The attempts of Ukrainian medievists to treat the history of Reformation first of all in socioeconomic and political aspects must be considered a progressive trend for that time. This trend was an evidence of advanced positivist methodology affecting the Ukrainian historiography since the middle of 19th century.